2017
DOI: 10.1002/2017jb014506
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Crustal Architecture Beneath the Sikkim Himalaya and Its Relationship to Active Deformation

Abstract: We study the 3‐D variation of the crustal structure of the Sikkim Himalaya using broadband seismological data acquired from a focused network of seven stations spanning the Lesser, Higher, and Tethyan Himalaya. Common conversion point stacking of receiver functions recorded along an across‐strike profile of the Himalaya reveals first‐order northward dip on the Main Himalayan Thrust (MHT), a midcrustal discontinuity and the Moho, along with higher‐order lateral variations. Three‐dimensional images generated fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 43 publications
9
24
0
Order By: Relevance
“…Joint inversion of receiver function and surface wave dispersion study in this region (Sharma et al, 2018) shows the MHT at 10-14 km for station BADR and 14-16 km in PHAG. Upwarping of the overlying thrusts due to the MHT structure were also reported in Sikkim (Paul & Mitra, 2017). West of our study region, the MHT is found at depths of 8-10 km (SMVD).…”
Section: Local Ramp Structures On the Underthrusting Indian Plate Betsupporting
confidence: 81%
See 2 more Smart Citations
“…Joint inversion of receiver function and surface wave dispersion study in this region (Sharma et al, 2018) shows the MHT at 10-14 km for station BADR and 14-16 km in PHAG. Upwarping of the overlying thrusts due to the MHT structure were also reported in Sikkim (Paul & Mitra, 2017). West of our study region, the MHT is found at depths of 8-10 km (SMVD).…”
Section: Local Ramp Structures On the Underthrusting Indian Plate Betsupporting
confidence: 81%
“…The steep dip of the Kishtwar thrust (as reported in Singh, 2010) compares well with the steep ramp of the MHT beneath the NE cluster of events, while the gentler dip of MCT (Singh, 2010) is similar to the gentle dip of MHT beneath the SW cluster of events. The capability of lateral heterogeneities terminating rupture propagation were discussed in detail for subduction scenarios in Wang and Bilek (2011) and its applicability to the MHT in the Sikkim Himalaya in Paul and Mitra (2017). Bilham et al (2013) and Schiffman et al (2011) reported normal faults in the SE edge of Kashmir Valley (33.56 ∘ N, 75.51 ∘ E) ∼30 km NW of the location of the M L 4.0 normal fault earthquake in this study.…”
Section: Local Ramp Structures On the Underthrusting Indian Plate Betmentioning
confidence: 65%
See 1 more Smart Citation
“…However, the lateral variation in Q 0 perturbation differentiates the Sikkim Himalaya (with low Q 0 ) from the Eastern Himalaya (with intermediate Q 0 ). This variation in attenuation is possibly a result of the upwarping and arcuate shape of the Himalayan thrust sheets beneath the Sikkim Himalaya (Paul & Mitra, ), which has not been reported from the Bhutan Himalaya (Diehl et al, ). The southern Tibetan Plateau is marked by low V s and low Q 0 perturbations due to elevated temperatures and presence of partial melts within the crust (Nelson et al, ; Priestley & McKenzie, ), which results in anelastic attenuation.…”
Section: Discussionmentioning
confidence: 94%
“…However, Sheehan et al () observed low attenuation of seismic shear waves in the uppermost mantle beneath the Higher Himalaya of eastern Nepal, which corresponds to low temperatures and hence brittle conditions. Further, Paul and Mitra () noticed a low velocity layer in the lower crust beneath the Higher Himalaya.…”
Section: Discussionmentioning
confidence: 97%